“Comparative impact of body mass index, waist circumference, and a body shape index on surgical difficulty in laparoscopic cholecystectomy: A cross-sectional comparative study” - Kumar, Hitesh; Swaroop Sanat Sahu; M Mundu; Ram Chandra Besra; Bodra, Pankaj; Toppo, Samir (Student’s Journal of Health Research Africa, 2025)
Background: Laparoscopic cholecystectomy (LC) is the preferred minimally invasive treatment for symptomatic gallstones, but surgical difficulty can vary, sometimes causing complications or conversion to open surgery. Traditional obesity assessment using Body Mass Index shows inconsistent predictive value, whereas waist circumference (WC) and A Body Shape Index (ABSI) may more accurately reflect body fat distribution and associated surgical risk. Aim: To comparatively assess the impact of BODY MASS INDEX, WC, and ABSI on surgical difficulty during LC. Methods: A cross-sectional comparative study was conducted over 2 years in the Department of General Surgery, Rajendra Institute of Medical Sciences, Ranchi. A total of 200 patients undergoing elective LC were enrolled. Preoperative anthropometric measurements (body mass index, WC, ABSI) were recorded. Intraoperative outcomes such as operative duration, complications, surgeon’s subjective difficulty scores, and conversion to open surgery were documented. Statistical analysis was performed using SPSS version 25. Chi-square test, Kruskal-Wallis test, and Binary Logistic Regression were applied. A p-value <0.05 was considered significant. Results: The majority of cases (61.5%) were classified as mild difficulty, 21.5% moderate, and 17% severe. WC was significantly associated with overall surgical difficulty (p=0.036) and physical stress experienced by the surgeon (p=0.014). Body mass index and ABSI did not show significant correlations with overall difficulty or specific surgical steps (all p > 0.05). Weight alone showed significant correlation with difficulty in approach to gallbladder (p=0.028), dissection of Calot’s triangle (p=0.029), and gallbladder removal/retrieval (p=0.042). Port insertion difficulty was not significantly associated with any parameter. Conclusion: WC was a more reliable predictor of surgical difficulty in LC compared to BODY MASS INDEX and ABSI. Weight also influenced the difficulty in specific steps. Recommendations: Preoperative assessment of WC should be incorporated into surgical planning for LC. Multicentric studies with larger cohorts are needed for validation.